2018
DOI: 10.4103/ajns.ajns_51_16
|View full text |Cite
|
Sign up to set email alerts
|

Acute subdural hematoma evacuation: Predictive factors of outcome

Abstract: Background: Acute subdural hematoma (aSDH) is a major cause of admission at Neurosurgical Emergency Department. Nevertheless, concerns regarding surgical indication in patients with multiple comorbidities, poor neurological status, antithrombotic therapy, and older age still persist. Therefore, a correct recognition of predictive outcome factors at hospital discharge is crucial to an appropriate neurosurgical treatment. Methods: Eighty-nine medical records of consecutive patients with age ≥18 years old who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
20
0
5
Order By: Relevance
“…The small number of females might be misrepresentative of this gender; however, this limitation has been observed in the majority of prior studies. The outcome after TBI might be influenced by patient's comorbidity such as diabetes mellitus, hypertension, dyslipidemia, smoking, chronic obstructive pulmonary disease, and heart disease; however, our data could be unique in terms of patient age in comparison to prior studies from other countries [ 14 18 ] as the mean age in our cohort is 34 ± 14 which precludes the presence of high proportion of comorbidities. However, diabetes mellitus and hypertension were found in 11.8%, and multivariate analysis showed that they did not have a significant predictor role for mortality.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The small number of females might be misrepresentative of this gender; however, this limitation has been observed in the majority of prior studies. The outcome after TBI might be influenced by patient's comorbidity such as diabetes mellitus, hypertension, dyslipidemia, smoking, chronic obstructive pulmonary disease, and heart disease; however, our data could be unique in terms of patient age in comparison to prior studies from other countries [ 14 18 ] as the mean age in our cohort is 34 ± 14 which precludes the presence of high proportion of comorbidities. However, diabetes mellitus and hypertension were found in 11.8%, and multivariate analysis showed that they did not have a significant predictor role for mortality.…”
Section: Discussionmentioning
confidence: 75%
“…This higher rate of acute traumatic SDH among males than females was also reported in many previous studies from different countries. For instance, the proportions of affected males were 52% (Portugal), 53% (Italy and Spain), 64% (Japan), 65% (the USA), and 74% (Brazil) [ 14 18 ]. However, there is no reported explanation in the literature for such gender discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that approximately 5.3 million people in the USA and approximately 7.7 million people in the European Union are living with disabilities related to TBI [3,4]. Acute subdural haematoma (ASDH) is one of the most harmful forms of TBI [5][6][7]. The haemorrhage is located in the subdural space and is often associated with a contusion or an intracerebral haematoma [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Acute subdural haematoma (ASDH) is one of the most harmful forms of TBI [5][6][7]. The haemorrhage is located in the subdural space and is often associated with a contusion or an intracerebral haematoma [3,6]. A traumatic ASDH can be treated either surgically or conservatively.…”
Section: Introductionmentioning
confidence: 99%